Public image and perception: the enlistment and struggles of women as World War II WAACs/WACs - Cashman, Kimberly Ann-Joubert (Kansas State University, 2019)
Women have been in integral part of history that has been decidedly left out of the picture until the last few decades. As history has been re-casted to include the contributions of women, this work examines the struggles endured by the American women who joined the Women’s Army Auxiliary Corps and/or the Women’s Army Corps during World War II. Using a limited investigation into the newspaper coverage in the New York area and personal comments WAAC/WAC veterans, this report argues that early press coverage of women soldiers belittled and humiliated them, thus discouraging women from enlisting. Over time, coverage became more positive as journalists gradually accepted the importance of women’s contributions to the military. By 1943, coverage was increasingly positive and articles about WACs received more prominent placement in newspapers. This shift occurred at the same time the number of women enlisting grew, suggestion the two are related. It was through the changes in the expected traditional proper place of women to a more realistic acknowledgment of the legitimacy of women’s work in the military that helped lay the platform to more permanent positive changes for women in the workplace, society, and at home.
Keywords: Military history; Women's history; American history; Military studies; Journalism